Hubungan Karakteristik dengan Pengetahuan Kesehatan Reproduksi pada Calon Pengantin di Kecamatan Banjarsari Kota Surakarta - Bilqis Rahma Yantika; Kusuma Estu Werdani (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
Adequate reproductive health knowledge among prospective brides serves as a crucial foundation in preventing various maternal and neonatal health problems, such as anemia, stunting, and pregnancy complications. This study aims to examine the relationship between sociodemographic characteristics (education, age, occupation) and the level of reproductive health knowledge among prospective brides. The research method a cross-sectional design with a sample of 102 registered prospective brides at the Banjarsari Religious Affairs Office (KUA) in Surakarta during the April-May 2025 period. Data collection utilized a questionnaire that had been tested for validity and reliabilty, at the data were statistically analyzed using the chi-square test. The results indicate that the majority of respondents had reproductive health knowledge in the high category (62%). However, bivariate analysis revealed no statistically significant relationship between reproductive health knowledge and the variables of education (p-value=0,935), age (p-value=0,447), or occupational (p-value=0,507). These findings suggest that sociodemographic factors are not the primary determinants of reproductive knowledge among prospective brides. Further research is recommended to explore other potential factors influencing reproductive health knowledge levels, such as exposure to media information, the quality of premarital counseling implementation, family support, and individual motivation in preparing for marriage.